Engineering tripartite gene editing machinery for highly efficient non-viral targeted genome integration - Hangu Nam; Keqiang Xie; Ishita Majumdar; Jiao Wang; Shaobo Yang; Jakob Starzyk; Danna Lee; Richard Shan; Jiahe Li; Hao Wu (Nature Communications)
Abstract Non-viral DNA donor templates are commonly used for targeted genomic integration via homologous recombination (HR), with efficiency improved by CRISPR/Cas9 technology. Circular single-stranded DNA (cssDNA) has been used as a genome engineering catalyst (GATALYST) for efficient and safe gene knock-in. Here, we introduce enGager, an enhanced GATALYST associated genome editor system that increases transgene integration efficiency by tethering cssDNA donors to nuclear-localized Cas9 fused with single-stranded DNA binding peptide motifs. This approach further improves targeted integration and expression of reporter genes at multiple genomic loci in various cell types, showing up to 6-fold higher efficiency compared to unfused Cas9, especially for large transgenes in primary cells. Notably, enGager enables efficient integration of a chimeric antigen receptor (CAR) transgene in 33% of primary human T cells, enhancing anti-tumor functionality. This ‘tripartite editor with ssDNA optimized genome engineering (TESOGENASE) offers a safer, more efficient alternative to viral vectors for therapeutic gene modification.